2012
DOI: 10.1074/jbc.m112.406637
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome Proliferator-activated Receptor-γ Activation Enhances Insulin-stimulated Glucose Disposal by Reducing ped/pea-15 Gene Expression in Skeletal Muscle Cells

Abstract: Background: PPAR␥ modulation of glucoregulatory response in skeletal muscle has been only partially elucidated. Results: PPAR␥ inhibits the transcription of the diabetes-associated gene ped/pea-15 via AP-1. Conclusion: ped/pea-15 is downstream of a PPAR␥-regulated inflammatory network. Significance: These studies further elucidate the gene network responsible for inflammation-induced insulin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…Indeed, recent work from our group has shown over-expression of Ped/pea-15 mRNA in the tibialis skeletal muscle of C57Bl/6 mice in which obesity is induced by high fat (HFD) feeding [14]. We now report that the D4 treatment improves insulin sensitivity in HFD induced obese C57BL/6 mice, with no effect on the body weight of animals.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Indeed, recent work from our group has shown over-expression of Ped/pea-15 mRNA in the tibialis skeletal muscle of C57Bl/6 mice in which obesity is induced by high fat (HFD) feeding [14]. We now report that the D4 treatment improves insulin sensitivity in HFD induced obese C57BL/6 mice, with no effect on the body weight of animals.…”
Section: Discussionmentioning
confidence: 67%
“…Recent observation by Ungaro P. et al demonstrated that Ped/pea-15 mRNA expression is increased by 2-fold in the tibialis skeletal muscle tissue of 6 month old diet-induced obese C57BL/6 mice [14]. Therefore, we investigated if Ad-D4 may improve insulin sensitivity also in this model.…”
Section: Resultsmentioning
confidence: 89%
“…Real-time PCR analysis Total RNA extraction, cDNA synthesis and real-time PCR were performed as described in Ungaro et al [26]. Relative quantification of gene expression was calculated by the ΔΔC t method [27].…”
Section: Methodsmentioning
confidence: 99%
“…Western blot and nuclear extract preparation Cell lysis, nuclear extract preparation and western blot for protein expression analysis were performed as described in Ungaro et al [26] and Dignam et al [29]. Immunoblots were performed using primary antibodies for PREP1 (1:1000; # sc-25282 Santa Cruz Biotechnology, Dallas, TX, USA) and NF-κB p65 (1:1000; # sc-8008) and for phosphorylated 5′ AMPactivated protein kinase (pAMPK) (1:1000; # 2531 Cell Signaling Technology, Danvers, MA, USA) and AMPK (1:1000; # 2532 Cell Signaling Technology), with β-actin (1:1000; # sc-1616) or lamin A/C (1:1000; # sc-20681) as loading control.…”
Section: Methodsmentioning
confidence: 99%
“…Rather, the epigenetic changes often modify chromatin structure and gene accessibility to the transcription machinery [2]. Thus, environmental factors may also epigenetically impact on genes which play an important role in the physiological control of glucose tolerance [3][4][5], even when these genes have not been recognized in previous genome-wide efforts or their function in energy homeostasis is indirect [6,7]. Similar to genetic polymorphisms [8], epigenetic modifications may alter the transcriptional activity of these genes and contribute to the insulin resistance, beta-cell and fat tissue dysfunction and type 2 diabetes phenotype, including response to anti-diabetic agents and occurrence of diabetes complications [9][10][11].…”
Section: Introductionmentioning
confidence: 98%